Gymneme Sylvestre as a Green Corrosion Inhibitor for Aluminum in an Acidic Medium - Bashir,S. (2021)
Abstract The corrosion inhibition property of Gymneme Sylvestre on aluminum in an acidic medium has been investigated. The experimental techniques include potentiodynamic polarization studies, electrochemical studies, quantum chemical calculation and weight loss method. The results revealed that Gymneme Sylvestre acts as a potential corrosion inhibitor of aluminum in an acidic medium, showing 82% inhibition efficiency at 800 ppm concentration of it. Furthermore, the different thermodynamic parameters, including activation energy, Gibbs free energy and enthalpy have been calculated. The results showed that adsorption of the Gymneme Sylvestre molecule onto the aluminum coupon surface obeys Langmuir adsorption isotherm. The quantum chemical parameters were also calculated for major constituents of Gymneme Sylvestre.